A saúde dos idosos brasileiros às vésperas do século XXI: problemas, projeções e alternativas Health of the Brazilian elderly population on the eve of the 21st century: current problems, forecasts and alternatives - Flávio Chaimowicz (Universidade de São Paulo, 1997)
São analizadas as características atuais e as perspectivas dos processos de transição demográfica e epidemiológica no Brasil. Foram utilizados os resultados do censo demográfico de 1991 e 1996 e Pesquisa Nacional por Amostra de Domicílios (PNAD) de 1993 e 1995, de novas projeções populacionais, e de recentes estudos sobre o perfil socioeconômico e de saúde de idosos de três grandes capitais brasileiras. Embora se estime que a proporção de idosos deverá duplicar até 2050, alcançando 15% do total da população, doenças crônico-degenerativas e distúrbios mentais já têm determinado, atualmente, maciça utilização dos serviços de saúde. O desenvolvimento de doenças, incapacidades e dependência têm sido mais freqüentes dentre aqueles de baixa renda que, no entanto, não têm conseguido garantir a assistência social e de saúde que demandam. Ações preventivas devem ser coordenadas por unidades básicas de saúde, priorizando necessidades locais. É imprescindível o investimento imediato na saúde, educação e formação técnica dos jovens, nos programas de apoio aos familiares e na manutenção de idosos em atividades produtivas adequadas. Current characteristics and perspectives of Brazilian demographic and epidemiological transition processes are analyzed. Results from the 1991, 1993, 1995 and 1996 censuses, new population projections and recent studies on socioeconomic and health profiles of elderly people of S. Paulo, Rio de Janeiro and Belo Horizonte are discussed. In 1995, estimated life expectancy at birth in Brazil was already over 67 years. The number of individuals aged 60 years and older - in 1995, 8.3%, of the total population - is expected to duplicate and probably stabilize by the year 2050. Yet lacking coverage and quality, health services are already burdened with degenerative diseases and mental disorders, frequent out-patient appointments, high hospital bed occupation and high costs. Functional impairment and self-reported diseases are related to poverty among the elderly, for whom social and health support are not properly provided. Support from informal caregivers becomes more difficult due to impoverishment, family size reduction and youth migration. Institutionalization remains a poor approach as scarcity of beds and inadequacy of staff preclude its utilization. To minimize the impact of population aging on health services, it is proposed that effective programs covering the control of degenerative diseases and the prevention of their complications should be implemente - for the elderly population too. The importance of physical exercise, screening for neoplastic diseases, immunization, prevention of fractures caused by falls and early diagnosis of depression and dementia is emphasized. Actions must be coordinated by primary health care units, oriented towards local needs. It is essential to maintain the elderly in adequate, productive activities, invest in young people's education and health and in social and medical support programs for the caregivers.